2006
DOI: 10.1007/11736639_65
|View full text |Cite
|
Sign up to set email alerts
|

Learning Online: A Comparative Study of a Situated Game-Based Approach and a Traditional Web-Based Approach

Abstract: Abstract. "Online Learning" has been commonly viewed as a mechanism for empowering improved learning outcome, increased flexibility of aligning the individual need of learners, and better quality of educational interaction. In fact, a lot of "digitized" and "ready-to-use" learning and teaching resources are already available online; nevertheless, we must not confuse quantity and quality, as these resources may just continue to perpetuate teacher-centred approaches, rather than student-centred approaches. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Since video games have such an important potential in stimulating motivation, can we apply them to education, making learning more interesting and inspiring learners' deep learning motivation? Plenty of empirical studies have shown (Jong, Shang, Lee, Lee, & Law, 2006; Barab et al, 2011; Huang & Huang, 2015; Furió et al, 2015) that game‐based learning is indeed better than traditional learning. Game‐based learning can mobilize the enthusiasm of the learners and promote motivation.…”
Section: What Are the Outcomes And Benefits Of Educational Games?mentioning
confidence: 99%
“…Since video games have such an important potential in stimulating motivation, can we apply them to education, making learning more interesting and inspiring learners' deep learning motivation? Plenty of empirical studies have shown (Jong, Shang, Lee, Lee, & Law, 2006; Barab et al, 2011; Huang & Huang, 2015; Furió et al, 2015) that game‐based learning is indeed better than traditional learning. Game‐based learning can mobilize the enthusiasm of the learners and promote motivation.…”
Section: What Are the Outcomes And Benefits Of Educational Games?mentioning
confidence: 99%
“…Video and computer games provide the pleasure and motivation of learning to young people who are already familiar with digital technology. Jong et al 13 depicted that game-based learning could reduce the frequently received negative feedback of Web-based learning regarding no motivation. Dziabenko and Pivec et al 6 designed a Web-based game for learning and showed that it can be very helpful for adult vocational or university-level learning as well as teaching children.…”
Section: Web-based Learning Gamementioning
confidence: 99%
“…If game-based learning is combined with the traditional methods of learning, the effectiveness of the learning could be greatly improved. 13 Web-based games mostly depend on Web technology. Web technology makes it possible to connect to Web-based games from anywhere the Internet is available and to play the games with others.…”
Section: Web-based Learning Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the advantages of the Volume 5, No. 1, October, 2012 sensory and contextual design, the educational games can stimulate students' motivation and interest in learning more efficiently (Dede et al, 2002;Jong et al, 2006), and increase kids critical thinking, cooperation, and problemsolving skills (Bruckman, 1998;Prensky, 2000). Playing games can also teach students more knowledge and provide learning that is deep, sustained and transferable to the real world .…”
Section: Introductionmentioning
confidence: 99%